2023
DOI: 10.21608/mjcu.2023.319011
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between the Levels of Serum Cystatin C and the Occurrence of the No-Reflow Phenomenon during Primary Percutaneous Coronary Interventions

RASHA ADEL THABET ROFYDA O. FATHALLAH,
ABDELRAHMAN E. ATTIA, M.D. and HOSSAM EL-DIN E.M. FARRAG, M.B.B.Ch.;

Abstract: Background:The best treatment of ST-segment elevation myocardial infarction (STEMI) is reperfusion of ischemic myocardium as soon as possible. Primary percutaneous coronary intervention (PPCI) has become the preferred strategy for reperfusion and the current standard care for STEMI. Noreflow is clinically important as it is associated with cardiac failure, malignant arrhythmias and in-hospital and long-term mortality. Cystatin C is a potent inhibitor of lysosomal proteinases and found in virtually all tissues … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
1
0
0
Order By: Relevance
“…Another study found an independent association between Cys-C and NRP in 68 STEMI patients. 31 In our study, we observed similar results in patients with NST-ACS. Several mechanisms may elucidate the potential role of Cys-C in patients with ACS and its association with NRP.…”
Section: Resultssupporting
confidence: 85%
“…Another study found an independent association between Cys-C and NRP in 68 STEMI patients. 31 In our study, we observed similar results in patients with NST-ACS. Several mechanisms may elucidate the potential role of Cys-C in patients with ACS and its association with NRP.…”
Section: Resultssupporting
confidence: 85%